Edukasi Bahaya Merokok pada Warga Dusun II Desa Watas Marga Kabupaten Rejang Lebong Provinsi Bengkulu - Nora Erlina; Rahayu Nofriyanti; Eva Susanti; Alimah Alimah; Yatri Hilinti (Utami Publisher, 2025)
Smoking is a major risk factor for Non-Communicable Diseases (NCDs) and contributes substantially to morbidity and mortality in Indonesia. The high prevalence of active smokers in rural areas highlights the need for more intensive and targeted health education. This community service activity aimed to improve the knowledge of residents in Dusun II, Watas Marga Village, regarding the dangers of smoking, the impact of second-hand smoke on family members, and initial steps toward smoking cessation. The intervention consisted of interactive counseling, group discussions, demonstrations of the effects of cigarette smoke on the lungs, and the distribution of educational leaflets. Evaluation was conducted through pre–post tests and participatory observation to assess changes in knowledge and attitude. The results showed a significant increase in participants’ knowledge, with the proportion of those in the “good” category rising from 28.6% to 82.9% after the educational session. Additionally, several residents expressed commitment to reducing cigarette consumption and implementing smoke-free home practices. This activity demonstrates that community-based health education is effective in increasing awareness and motivation to prevent smoking-related health risks.